PREDICTION OF WORK STRESS, LEADERSHIP QUALITY, MOTIVATION OF WORK AND ORGANIZATION CULTURE TO WORK SATISFACTION AND IMPACT ON TURNOVER INTENTION EMPLOYEES - Pande Putu Buda Prasada; Ni Nyoman Sawitri (Jurnal Manajemen dan Pemasaran Jasa, 2019)
This research aimed to analyze and predict how work stress factors, quality of leadership, work motivation, organizational culture, and job satisfaction affect the turnover intention. Observations on this research were conducted on 150 employees in national companies engaged in satellite-based telecommunications. Data were collected by using questionnaire. The analysis method used Structural Equation Model (SEM) with Partial Least Square(PLS) as an analysis tool. The research results showed that work stress and job satisfaction influence on turnover intention while the quality of leadership, work motivation, and organizational culture have no effect on turnover intention. Suggestions for future research and the company are outlined in the closing section.